Assessment Of Antimicrobial Efficacy Of Kabasura Kudineer Choornam Against Common Oral Microbes – A Randomised Invitro Study On Biofilm Model (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess the antimicrobial efficacy of Kabasura Kudineer Choornam against common oral microbes in an invitro biofilm model. Materials and methods: An experimental in-vitro study was done to assess the antimicrobial property of Kabasura Kudineer Choornam (Test product) against 0.2% Chlorhexidine (Positive control), Distilled water (Negative control).The zone of inhibition and minimum inhibitory concentration was assessed using disk diffusion method.36 single rooted teeth were collected and the selected organisms such as S.mutans, L.acidophillus, E. faecalis, C. albicans were procured and cultured in the selective medium. After superficial removal of debris from the tooth samples, the teeth were stored in Brain Heart Infusion agar and later microbial suspension was added to form a biofilm incubating for 7 days. The tooth samples were then irrigated with saline and randomly divided and placed into test tubes containing, the test product, positive and negative control. The colony-forming units were procured with the microdilution obtained from the tooth samples. The antibiofilm efficacy was assessed on 16 teeth samples, which was then randomly divided into a positive and negative control. Under the positive control, the teeth samples were subjected to the microbial suspension along with the nutrient broth while the teeth samples in the positive control were subjected initially to the test product along with the nutrient broth followed by the microbial suspension and both the controls were incubated for 7 days. The antibiofilm efficacy was tabulated through the colony forming units using the microdilution from the tooth samples. Results: The test product Kabasura kudineer choornam failed to prove to an antimicrobial efficacy compared to the positive control 0.2% chlorhexidine mouthwash on a matured biofilm formed by the oral microbes. While assessing the ability of the test product against the biofilm formation, the test product had an antibiofilm effect on the teeth samples. Conclusion: Kabasura Kudineer Choornam proved to have less effect against the common oral microbes compared to the gold standard 0,2% chlorhexidine.